The Role of Leadership in Promoting Knowledge Sharing Practice in Matriculation Program (Ministry of Education Malaysia) - Mohamad Nain, Jusoh (2004)

(untitled)
Knowledge management is emerging as one the leading influences on an organization’s survival and competitive advantage. Knowledge management is concerned with the effective acquisition, sharing and utilization of knowledge. Corporate leaders are increasingly aware of the notion that an organization‘s longterm survival depends on its ability to generate new knowledge and continuously learn from the environment. In the knowledge management recent studies was found that the most crucial phase is a knowledge sharing process. There are two major factors in determining the effectiveness of knowledge sharing process that is psychological and social factor but this two factor has been identify was influence by the organization’s leader. The study is therefore aimed to examine perceive of subordinates (lecturers) on the characteristic of leader’s in promoting knowledge sharing practice in education institution as well as Matriculation Program. This information is gathered through mailed questionnaire on 214 lecturers in Matriculation Program throughout Malaysia. The finding indicates that intention to share knowledge shows significant differences based on experience and teaching option but not based on gender. The perceive of lecturers on leadership skills is more on leader’s interpersonal trust but share vision and be a role model are positively correlated with the intention to share knowledge. This may be a key component in leadership skill that will influence the process of knowledge sharing practice among lecturers especially in Matriculation Program and education institution in general. This research was recommended that leader which is director of college, should encourage and involve in any activities that regard to knowledge improvement, more conscious with the explosion of knowledge development especially tacit knowledge, continually develop interpersonal trust and practicing the share vision visibly.